The effect of digital technologies adoption in healthcare industry: a case based analysis. Issue 5 (12th July 2018) - Laurenza, Elena; Quintano, Michele; Schiavone, Francesco; Vrontis, Demetris
Abstract : Purpose: The purpose of this paper is to contribute to the extant literature regarding the exploitation of digital technologies by illustrating how this type of IT can influence business process improvements in the healthcare industry. Design/methodology/approach: The paper reports an illustrative case study for MSD Italy, the Italian subsidiary of the USA-based company Merck & Co., Inc. The group sells drugs for human use in Italy but is also active in the veterinary (MSD Animal Health) industry, with Vree Health, and in solutions and software-based services for the healthcare industry. Findings: The results show that the adoption of digital technologies could improve the performance of main healthcare business processes, particularly those processes that can be simplified with the adoption of information technology. More specifically, digital technologies could increase efficiency and, at the same time, allow for the delivery of better quality and reduced response times, with many benefits for several stakeholders, such as national health systems, clinicians and patients. Originality/value: Although some studies report the need for effective business processes for sustainable healthcare systems, there is a lack of literature regarding the specific implications of the adoption of such digital technologies for the business process management of healthcare firms. This paper attempts to fill in this gap.